To the mechanism of instability of cylindrical relativistic electron beam in plasma - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Vesnovskaya, M.S. (Вопросы атомной науки и техники, 2011)
The instability of relativistic electron beam of finite radius in plasma caused by predominantly transversal dynamics of electrons is investigated. The formation of a sequence of short relativistic electron bunches from a long bunch including shaped one is 2d3v-simulated.